The role of HCV proteins on treatment outcomes - Kattareeya Kumthip (2018)
© 2015 Kumthip and Maneekarn. For many years, the standard of treatment for hepatitis C virus (HCV) infection was a combination of pegylated interferon alpha (Peg-IFN-α) and ribavirin for 24-48 weeks. This treatment regimen results in a sustained virologic response (SVR) rate in about 50 % of cases. The failure of IFN-α-based therapy to eliminate HCV is a result of multiple factors including a suboptimal treatment regimen, severity of HCV-related diseases, host factors and viral factors. In recent years, advances in HCV cell culture have contributed to a better understanding of the viral life cycle, which has led to the development of a number of direct-acting antiviral agents (DAAs) that target specific key components of viral replication, such as HCV NS3/4A, HCV NS5A, and HCV NS5B proteins. To date, several new drugs have been approved for the treatment of HCV infection. Application of DAAs with IFN-based or IFN-free regimens has increased the SVR rate up to > 90 % and has allowed treatment duration to be shortened to 12-24 weeks. The impact of HCV proteins in response to IFN-based and IFN-free therapies has been described in many reports. This review summarizes and updates knowledge on molecular mechanisms of HCV proteins involved in anti-IFN activity as well as examining amino acid variations and mutations in several regions of HCV proteins associated with the response to IFN-based therapy and pattern of resistance associated amino acid variants (RAV) to antiviral agents.